Experimental Approach to the Direct Interaction Between the H2O-CO2 Atmosphere and the Crust on the Earliest Earth: Implications for the Early Evolution of Minerals and the Proto-Atmosphere - Hao, Xi-Luo; Li, Yi-Liang (Frontiers in Earth Science, 2018)
Batch experiments between solid materials including komatiite, peridotite and basalt with an H2O-CO2 atmosphere were performed at temperatures from 200°C to 500°C to simulate the interaction between the new rocky crust formed after the magma ocean stage and the concurrent proto-atmosphere of the early Earth. Electron microscopic observations show that clay mineral flakes were generated in all experiments. In komatiite/peridotite reaction systems, fibrous actinolite was generated in experiments conducted at higher temperatures (>400°C). Different carbonate species were produced in experiments conducted at temperatures no higher than 400°C. Formation of these carbonates and their diverse crystal habits may indicate varied extraction rates of calcium, magnesium and SiO2 from the original ultramafic rocks resulted from different experimental temperatures. Our results imply that clay minerals and carbonates could probably be formed extensively in the early Hadean by the intense interaction between the ultramafic rocky crust and the H2O-CO2 atmosphere before the formation of the earliest ocean. Rapid sequestration of the atmospheric CO2 caused by the massive precipitation of carbonates might have led to the rapid cooling of the Earth’s atmosphere and the formation of the earliest oceans.